The Prospect of Neutron Scattering In the 21st Century: A Powerful Tool for Materials Research - E. Kartini (PPIKSN-BATAN, 2007)
Over the last 60 years research reactors (RRs) have played an important role in technological and socio-economical development of mankind, such as radioisotope production for medicine, industry, research and education. Neutron scattering has been widely used for research and development in materials science. The prospect of neutron scattering as a powerful tool for materials research is increasing in the 21st century. This can be seen from the investment of several new neutron sources all over the world such as the Spallation Neutron Source (SNS) in USA, the Japan Proton Accelerator Complex (JPARC) in Japan, the new OPAL Reactor in Australia, and some upgrading to the existing sources at ISIS, Rutherford Appleton Laboratory, UK; Institute of Laue Langevin (ILL) in Grenoble, France and Berlin Reactor, Germany. Developing countries with moderate flux research reactor have also been involved in this technique, such as India, Malaysia and Indonesia. The Siwabessy Multipurpose Reactor in Serpong, Indonesia that also produces thermal neutron has contributed to the research and development in the Asia Pacific Region. However, the international joint research among those countries plays an important role on optimizing the results.